Europeizacija ir kintanti politinės komunikacijos kultūra Baltijos šalyse - Vinciūnienė, Aušra (Information & Media, 2012)
Pastaraisiais metais itin išpopuliarėjusių Europos Sąjungos (ES) politinės komunikacijos tyrimų centre atsidūrė mokslininkų pastangos atskleisti europeizacijos kontekste naujai išryškėjančius savitus sociokultūrinio konteksto nulemtus dalykus. Šiame straipsnyje, remiantis kokybinio tyrimo (atlikto 2006–2009 m.) rezultatais, analizuojami politinės komunikacijos europeizacijos procesai dviejose Baltijos šalyse (Lietuvoje ir Estijoje) – naujosiose ES narėse, jaunos demokratijos valstybėse, apie kurių kontekstą ir patirtis Europos moksliniame diskurse pernelyg mažai žinoma. Tyrimas parodė, kad Baltijos šalyse metams bėgant palaipsniui pradėjo formuotis ne tik tam tikra atskira europinės komunikacijos dimensija, bet ir savita kultūra: galima stebėti, kaip ji paveikė įprastas, nusistovėjusias politikos ir žiniasklaidos santykio praktikas, paskatino institucinės komunikacijos profesionalėjimą. Kita vertus, paaiškėjo, kad persiorientuoti prie labiau formalizuotos bei profesionalios ES politinės komunikacijos kultūros tapo dideliu iššūkiu abiem pusėms – tiek Lietuvos bei Estijos žurnalistams, tiek įvairių nacionalinių institucijų komunikacijos specialistams.Pagrindiniai žodžiai: europeizacija, ES komunikacijos politika, politikos ir žiniasklaidos santykis, politinės komunikacijos kultūra, Baltijos šalys.Europeanization and changing political communication culture in the Baltic statesAušra VinciūnienėSummaryThis article contributes to expanding the European public sphere research on the Europeanization processes taking place in the new EU member states. It argues that a qualitative shift from the national to the European dimension was, and still is, a great challenge to both societies and political and media actors in Central Eastern Europe.The qualitative research in two Baltic countries – Lithuania and Estonia (in 2006–2009) – has shown that there are some differences in the nature and pace of national (cultural) adaptation of the European perspective in day-to-day political reporting and institutional communication practices as compared with the old member states. The national governments and local institutions show no particular interest (taking into the account a very high support of the EU membership among citizens) and have no financial resources or professional competenc to invest in-to communication on European matters. The study disclosed also the absence of institutionalized “politics–media” relationship among national parties, governments and the media. From the perspective of political institutions, the mass media are an important channel for communication; however, national journalists are regarded by politicians as uncooperative, lacking skills, knowledge and interest in the EU politics. On the other hand, it became obvious that the Baltic media are primarily functioning on commercial logic: they seek to meet the audience demand for entertainment rather than invest into initiating political deliberations, the EU affairs being no exception.Finally, a significant problem is the EU communication policy itself: as the study has revealed, it does not correspond to the realities of the new EU member states where traditions of having consultations with citizens and social groups in the political decision-making process are only in the stage of formation. Still the Commission sees its mission in a more direct involvement with different groups of citizens on educating on what the EU is and how it functions, rather than having a more ambitious goal of communicating and fostering debates and deliberations.